APAKAH PROGRAM READSI DAPAT MENINGKATKAN PENDAPATAN PETANI? STUDI KOMPARASI PADA PETANI JAGUNG GORONTALO - Marjan, Nursella; Indriani, Ria; Adam, Echan (Universitas Galuh, 2023)
The research aims to analyze the income of com farmers in Gorontalo Regency and compare the income of corn farmers before and after joining the READSI (Rural Empowerment and Agricultural Development Scalling-up Initiative) program. The sample was determined using Purposive Sampling with 55 com farmers in Ayuhula Village, Dungaliyo Subdistrict, Gorontalo Regency. This research employs explanatory research with a quantitative and statistical approach. The data analalysis consists of the analysis of cost structure, income and revenue, and paired sample t-test comparison test. The results indicate that the average accumulation of income per farmer before the READSI program was IDR 7.823.516 per planting season. Meanwhile, the average income per farmer after participating the READSI program was IDR 19.313.524 per planting season. Statistically, the farmers’ income after joining the READSI program is significantly different from their income before participating in the program. The average income difference per farmer from the READSI farmer group reaches 54%. In conclusion, the READSI program has proven to increase farmer productivity and ultimately improve farmer income in Gorontalo Regency.